Social Representations of Gynecologic Cancer Screening Assessment a Qualitative research on Ecuadorian women - Yolanda Godoy; Clara Godoy; Juan Reyes (SciELO, 2016)
The purpose of this work was to explore: knowledge, attitudes, and beliefs regarding gynecologic cancer screening on Ecuadorian women users of primary care facilities, to identify the social representations that users of health services make about these programs and their influence on the decision to undergo a screening. An exploratory and qualitative research design was held using focus groups and in-depth interviews for data collection. A narrative content analysis of the results was conducted. Women's knowledge on gynecological cancer screening was confusing. Most frequent misconceptions related to the pap smear were: the belief that it could be useful for detecting pregnancy, ovarian cysts or infections. Most of the participants stated that the pap smear procedure is a traumatic and painful experience. Regarding to mammography women said it was used for sick woman and this procedure by itself may cause cancer.